Association Between Burn Excision Timing and Mortality in ICU Burn Patients: A Two-Year Retrospective Study - Wardhana, Aditya; Farhana, Nadya; Leksono, Tiara Putri (Faculty of Medicine-Universitas Airlangga, 2026)
Introduction: Severe burn injuries requiring Intensive Care Unit (ICU) admission are strongly associated with high mortality, particularly in patients with extensive total body surface area (TBSA) involvement, sepsis, and mechanical ventilation. Surgical excision is widely recommended as a component of burn care. However, its association with survival in critically ill burn patients remains debated, especially in low-resource settings. Objectives: To evaluate the association between burn excision timing and mortality outcomes in ICU-admitted burn patients. Methods: This retrospective cohort study was conducted at a burn unit referral hospital in Jakarta, Indonesia, from January 2023 to December 2024, and included 130 ICU-admitted burn patients. The intervention was burn excision, either early or delayed, compared with nonoperative management. Data were analyzed to determine mortality outcomes using chi-square testing, with p < 0.05 considered significant. Results: Among the included patients, most sustained flame burns involving more than 40% TBSA, with burn depth ranging from superficial dermal to full-thickness. Surgical burn excision was performed in 71.5% of cases. Mortality occurred in 44 patients in the early excision group, with early tangential excision conducted in 52.3% (68/130). Delayed excision, primarily due to late presentations and referral system delays, was performed in 25 patients with 10 deaths. Of the 35 patients who did not undergo excision, 32 died prior to surgical intervention. Statistical analysis revealed a significant association between excision timing and mortality outcome (p < 0.001), suggesting that surgical excision was associated with improved survival compared to non-operative care. Conclusion: These findings suggest that burn excision is associated with improved survival in critically ill populations. However, the retrospective design and survivor bias mean this association is not causal.